FILSAFAT ETIKA IBN MISKAWAIH - Abdul Hakim (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2014)
Ibn Miskawayh is one of the Islamic philosophers who focused on the study of ethics. In his Tahdheeb al-Akhlaqhe reflects on the concept of ethics systematically using Greek philosophy and combine it with the Quran and hadith.Although compared to the concept of ethics of Immanuel Kants deontology, ethics Ibn Miskawayh not apply well tothe rule of law. However, the severity of the effort is a big contribution on the development of ethical discourse thatconnects rational ethics and ethical revelation.